VD_FINDINFO Décision / 2014 / 675 vom 13. August 2014 - VD Tribunal cantonal (2014)
RISQUE DE RÉCIDIVE, SOUPÇON, PROPORTIONNALITÉ, DÉTENTION PROVISOIRE, MESURE PROVISIONNELLE | 221 al. 1 let. c CPP (CH), 237 CPP (CH)